STRATEGI SENTRA INDUSTRI TENUN TRADISIONAL SARUNG GOYOR DESA POJOK DALAM MENDUKUNG PROGRAM PEMBANGUNAN BERKELANJUTAN DESA - anggraeni, yunia; Rahman, Abdul; Yuhastina, Yuhastina (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Sustainable Development Goals (SDGs Desa), is a program that invites all villages in Indonesia to play an active role in village development by raising the characteristics, potential and local wisdom of each village. Based on the 18th goal of the Village SDGs, each village can express development into something more flexible according to village conditions. Such as in Corner Village, Sukoharjo Regency, Central Java Province, which has a superior product in the form of Goyor Sarong. The production process still uses the traditional method, namely using a tool called ATBM (Non-Machine Loom). This research uses a qualitative approach. Data collection techniques are carried out by interviews, observations and documentation. The study involved 14 informants, consisting of industry owners and their employees. The results showed that the Goyor Sarong Industrial Center can support the Village SDGs program because the strategies implemented by industry players in maintaining the continuity of Goyor Sarong production already include three main pillars in Sustainable Development, namely the social, economic and environmental pillars. The social pillar is shown by the existence of equal employment opportunities for the community, free weaving training, contributing to educational interests, and good cooperation between industry owners. The economic pillar is proven by maintaining the quality of production, online marketing, participating in exhibitions, and collaborating with various parties. Environmental pillars, namely using the highest quality dye medicines, providing waste shelters, striving for innovation in the use of waste from natural materials, and collaborating with factories in Pekalongan in staining warp yarns